2014
DOI: 10.1586/14737140.2014.895937
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer: current standards, working towards a new therapeutic approach

Abstract: Pancreatic cancer is the fourth leading cause of cancer deaths with a 5-year survival of 4–6%. Clinical challenges remain to be addressed, since few promising approaches to treat pancreatic cancer have been reported. Here we discuss the potential of a new biotherapeutic agent composed of a lysosomal protein (Saposin C, SapC) and an acidic phospholipid (dioleoylphosphatidylserine, DOPS) which can be assembled into stable nanovesicles (SapC-DOPS) for tackling pancreatic cancer. Phosphatidylserine (PS) is a lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In vitro, the cytotoxic effect of SapC-DOPS correlated with surface PS expression on cells. Our studies have demonstrated that SapC-DOPS selectively induces apoptotic cell death in malignant pancreatic cells, whereas untransformed pancreatic ductal epithelial cells remain unaffected [13][14][15]38]. Furthermore, animals with xenograft tumors treated with SapC-DOPS showed clear survival benefits and reduced tumor size compare to untreated mice.…”
Section: Theraeutic Studies Of Sapc-dops In Cancer Cellsmentioning
confidence: 66%
“…In vitro, the cytotoxic effect of SapC-DOPS correlated with surface PS expression on cells. Our studies have demonstrated that SapC-DOPS selectively induces apoptotic cell death in malignant pancreatic cells, whereas untransformed pancreatic ductal epithelial cells remain unaffected [13][14][15]38]. Furthermore, animals with xenograft tumors treated with SapC-DOPS showed clear survival benefits and reduced tumor size compare to untreated mice.…”
Section: Theraeutic Studies Of Sapc-dops In Cancer Cellsmentioning
confidence: 66%
“…Pancreatic cancer is one of the most lethal human cancers with a 5year survival rate of about 4-6% [1]. Early detection could significantly achieve the best clinical outcomes.…”
Section: Commentarymentioning
confidence: 99%
“…SapC-DOPS NPs have so-called “fusogenic” activity with particles interacting with the endogenous PtdSer on cancer cells resulting in NP-cell fusion. PtdSer is highly expressed on tumor cells of certain cancers, especially high in pancreatic cancers [45], which allows for selective targeting of SapC-DOPS. SapC-DOPS contain phospholipid dioleoylphosphatidylserine (DOPS) and Saponin C (SapC), which is an 80 amino acid multifunctional glycoprotein expressed in the lysosomal membrane of all cell types.…”
Section: Therapy With Phosphatidylserine Carriersmentioning
confidence: 99%